MAIN SOURCE OF TEACHERS’ SELF-EFFICACY IN INDONESIAN TUTORIAL CENTRE’S TEACHERS: UNDERSTANDING PUPILS’ NEEDS - Wibawa, Cheryl G; Dahlan, Tina H; Budiman, Nandang (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This study is a preliminary research study on enhancing tutorial center teachers' self-efficacy through lesson study, which aims to identify sources of teachers' self-efficacy in facilitating engagement for students, implementing instructional practices, and managing the classroom, and their impacts on teaching and learning. The study used a qualitative content analysis method, and data were analyzed by hand. Data collection is from an online focus group and individual interviews with five tutorial center teachers with a small group learning method in Indonesia with eleven self-efficacy questions. The participants consisted of three female teachers of 22, 32, and 33 years old and two male teachers of 18 and 24. All teachers teach high school levels with various teaching experiences from six months to fourteen years. Their teaching subjects are consistent with their educational background; four teachers taught more than one subject, and one teacher taught only one subject. The finding shows tutorial center teachers' self-efficacy in facilitating student engagement, instructional practices, and classroom management, and understanding pupils' needs as the primary source of teachers' self-efficacy. Mastery experience is the other source of self-efficacy for tutorial center teachers. Teachers' self-efficacy affected their teaching performance and ability to promote proper time management and good communication skills.